Loan Repayment and Diversion among Anchor BorrowerProgramme’s Beneficiaries in Niger State, Nigeria (NTU Journal of Agriculture and Veterinary Science, 2024)
The Anchor Borrower Programme (ABP) involves the provision of farm inputs in kind and cash to small-holder farmers to boost production of targeted commodities. This study assessed loan repayment among ABP beneficiaries as well as to examine its diversion. A total of 138 farmers were randomly selected. Data was analysed using descriptive statistics. Results showed that majority (75.4%) of the beneficiaries were men with average age of 40 years with an average farm size of 1.7 hectares. Majority (85.5%) of the beneficiaries defaulted in repayment of the given loan. Although 43.5% and 14.5% of them made a partial and complete loan repayment respectively. Also, 28.3% of them payback with produce and cash while 18.1% and 16.7% of them payback with produce and cash only respectively. Furthermore, personal/familyneeds (62%) topped the reasons for loan diversion. Also, ?20% diverted the loan to serve other purposes. It was concluded that without proper management, the scheme would die. The study recommends that the scheme should be given better management in order to prevent diversion of funds as well as to ensure prompt repayment.